In situ collection of dust grains falling from Saturn’s rings into its atmosphere - Hsu, Hsiang-Wen; Postberg, Frank; Khawaja, Nozair A. (Science, 2018)
Cassini's final phase of exploration - The Cassini spacecraft spent 13 years orbiting Saturn; as it ran low on fuel, the trajectory was changed to sample regions it had not yet visited. A series of orbits close to the rings was followed by a Grand Finale orbit, which took the spacecraft through the gap between Saturn and its rings before the spacecraft was destroyed when it entered the planet's upper atmosphere. Six papers in this issue report results from these final phases of the Cassini mission. Dougherty et al. measured the magnetic field close to Saturn, which implies a complex multilayer dynamo process inside the planet. Roussos et al. detected an additional radiation belt trapped within the rings, sustained by the radioactive decay of free neutrons. Lamy et al. present plasma measurements taken as Cassini flew through regions emitting kilometric radiation, connected to the planet's aurorae. Hsu et al. determined the composition of large, solid dust particles falling from the rings into the planet, whereas Mitchell et al. investigated the smaller dust nanograins and show how they interact with the planet's upper atmosphere. Finally, Waite et al. identified molecules in the infalling material and directly measured the composition of Saturn's atmosphere. - Science, this issue p. eaat5434, p. eaat1962, p. eaat2027, p. eaat3185, p. eaat2236, p. eaat2382 - Structured Abstract - INTRODUCTIONDuring the Cassini spacecraft’s Grand Finale mission in 2017, it performed 22 traversals of the 2000-km-wide region between Saturn and its innermost D ring. During these traversals, the onboard cosmic dust analyzer (CDA) sought to collect material released from the main rings. The science goals were to measure the composition of ring material and determine whether it is falling into the planet’s atmosphere. - RATIONALEClues about the origin of Saturn’s massive main rings may lie in their composition. Remote observations have shown that they are formed primarily of water ice, with small amounts of other materials such as silicates, complex organics, and nanophase hematite. Fine-grain ejecta generated by hypervelocity collisions of interplanetary dust particles (IDPs) on the main rings serve as microscopic samples. These grains could be examined in situ by the Cassini spacecraft during its final orbits. Deposition of ring ejecta into Saturn’s atmosphere has been suggested as an explanation for the pattern of ionospheric infrared emission, a phenomenon known as ring rain. Dynamical studies have suggested a preferential transport of charged ring particles toward the planet’s southern hemisphere because of the northward offset of Saturn’s internal magnetic field. However, the deposition flux and its form (ions or charged grains) remained unclear. In situ characterization of the ring ejecta by the Cassini CDA was planned to provide observational constraints on the composition of Saturn’s ring system and test the ring rain hypothesis. - RESULTSThe region within Saturn’s D ring is populated predominantly by grains tens of nanometers in radius. Larger grains (hundreds of nanometers) dominate the mass density but are narrowly confined within a few hundred kilometers around the ring plane. The measured flux profiles vary with the CDA pointing configurations. The highest dust flux was registered during the ring plane crossings when the CDA was sensitive to the prograde dust populations (Kepler ram pointing) (see the figure). When the CDA was pointed toward the retrograde direction (plasma ram pointing), two additional flux enhancements appeared on both sides of the rings at roughly the same magnetic latitude. The south dust peak is stronger and wider, indicating the dominance of Saturn’s magnetic field in the dynamics of charged nanograins. These grains are likely fast ejecta released from the main rings and falling into Saturn, producing the observed ionospheric signature of ring rain.We estimate that a few tons of nanometer-sized ejecta is produced each second across the main rings. Although this constitutes only a small fraction (<0.1%) of the total ring ejecta production, it is sufficient to supply the observed ring rain effect. Two distinct grain compositional types were identified: water ice and silicate. The silicate-to-ice ratio varies with latitude; the global average ranges from 1:11 to 1:2, higher than that inferred from remote observations of the rings. - CONCLUSIONOur observations illustrate the interactions between Saturn and its main rings through charged, nanometer-sized ejecta particles. The dominance of nanograins between Saturn and its rings is a dynamical selection effect, stemming from the grains’ high ejection speeds (hundreds of meters per second and higher) and Saturn’s offset magnetic field. The presence of the main rings modifies the effects of the IDP infall to Saturn’s atmosphere. The rings do this asymmetrically, leading to the distribution of the ring rain phenomenon. Confirmed ring constituents include water ice and silicates, whose ratio is likely shaped by processes associated with ring erosion processes and ring-planet interactions. Download high-res image Open in new tab Download Powerpoint Schematic view of the nanometer-sized ring ejecta environment in the vicinity of Saturn.CDA measurements were taken during Cassini’s Grand Finale mission. The measured dust flux profiles, presented by the histograms along the spacecraft trajectory, show different patterns depending on the instrument pointing configuration. The highest dust flux occurred at the ring plane under Kepler ram pointing (yellow). The profiles registered with plasma ram pointing (green) show two additional, mid-latitude peaks at both sides of the rings with substantial north-south asymmetry. This signature in the vertical profiles indicates that the measured nanograins in fact originate from the rings and are whirling into Saturn under the dynamical influence of the planet’s offset magnetic field. Blue and orange dots represent the two grain composition types identified in the mass spectra, water ice and silicate, respectively. - Saturn’s main rings are composed of >95% water ice, and the nature of the remaining few percent has remained unclear. The Cassini spacecraft’s traversals between Saturn and its innermost D ring allowed its cosmic dust analyzer (CDA) to collect material released from the main rings and to characterize the ring material infall into Saturn. We report the direct in situ detection of material from Saturn’s dense rings by the CDA impact mass spectrometer. Most detected grains are a few tens of nanometers in size and dynamically associated with the previously inferred “ring rain.” Silicate and water-ice grains were identified, in proportions that vary with latitude. Silicate grains constitute up to 30% of infalling grains, a higher percentage than the bulk silicate content of the rings.
Gesehen am 09.10.2019